Pelatihan Pembuatan E-Modul dan E-Book Berbantuan Flipbook DI SMA N 15 OKU - Sugiarti Sugiarti; Patricia HM Lubis; Lukman Hakim; Sulistiawati Sulistiawati; Lefudin Lefudin; Linda Lia (Wahana Dedikasi : Jurnal PkM Ilmu Kependidikan, 2023)
The purpose of this community service activity is that through community service activities it is hoped that it can increase the insight of teachers so that they can carry out the media that it becomes better in learning process. In addition, variatif mmedia can also improve the ability of teachers to develop interactive media to increase quality result of study in cognitive, affective and psychomotor domains correctly. Media has main role to delivery information to student in order to give meaningfully study. Through this community service activity, teachers are given insight as well as technical skills to design e-modul and e-book are using flipbook. Based on the results of observations and questionnaire assessments from this activity, the activity went smoothly and received a positive response from teacher participants at SMA Negeri 15 OKU. Keywords: E- Modul, E-Book, Plifbook.